Experimental studies of forming design at dynamic load - Nazarenko, Ivan; Dedov, Oleg; Svidersky, Anatoly; Oryshchenko, Serhii (Technology audit and production reserves, 2018)
The object of research is the movement process of forming structures of a vibration unit with spatial oscillations. The main disadvantage of such vibration systems is the lack of data on the mutual influence of machines and media. Experimental vibration unit is developed and manufactured. The unit is equipped with two asymmetrically mounted vibration exciters that are attached directly to the forming surfaces. A new technique for measuring the motion of forming structures with the location of sensors in the areas of dynamic load is proposed. The basis of their location is the premise of determining the contact forces of the interaction of the subsystems with each other. As well as an assessment of the ratio of time of action and time of wave propagation. This approach is new, because it takes into account the real relationship of the dynamic parameters of the machine and the environment between them and the degree of interference. In the course of research, records of continuous fixation of the distribution of active oscillations of forming surfaces are used. A fundamentally new result is obtained, which consists in the fact that the transition process is envisaged to take into account when determining the parameters and locations of vibrators. Due to this, the forms of natural oscillations of the system with large amplitudes of oscillation and correspondingly lower frequency are realized. Compared with similar known designs of vibration units, this can significantly reduce the energy intensity of the causes of the vibration machine. The use of pneumatic generators in real factory conditions reduces the noise level and accelerates the speed of the process of compacting concrete. Practical recommendations for the rational constructive design of sections of forming structures are developed. Technological parameters of oscillations with new values of the output numerical values of the amplitude-frequency mode of the exciter of oscillations are determined. To construct such forming structures, the sites for vibration units are determined. The obtained results can be used in related processes, for example, in the mining industry, as active surfaces for transporting ore, for moving suspensions and solutions in the chemical industry.